Civil Liability of Notaries in The Execution of Bank Credit Agreement Deeds Based on Invalid or False Documents - Bimo Bimantoro; Sukarmi; Yenny Eta Widyanti (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
This study aims to analyze the limits of a notary’s civil liability in the preparation of banking credit agreement deeds based on materially inaccurate documents, as well as to examine the juridical implications for the validity of authentic deeds and the legal relationships between the parties. The research employs a normative legal method with statutory, conceptual, and case approaches, supported by an analysis of banking regulations, the Civil Code, and the Notary Position Act. The results indicate that, in principle, a notary is only responsible for the formal validity of the deed, insofar as all procedures and statutory requirements have been fulfilled. However, under certain circumstances, a notary may be held civilly liable if proven to have acted negligently, carelessly, or in violation of the duty of prudence. Furthermore, the use of materially inaccurate documents may lead to defects of consent, unlawful acts, and the degradation of the evidentiary strength of an authentic deed into that of a private document. Therefore, it is necessary to establish clearer normative boundaries regarding the extent of material verification by notaries in order to ensure legal certainty and protection for the parties in banking credit practices. This study also emphasizes the importance of harmonizing the prudential banking principle with notarial authority to prevent an imbalance of legal responsibility that may adversely affect financial institutions and the public at large. In addition, it provides normative recommendations to clarify the scope of notarial liability in the future.